Low temperature hydrogenation of tetralin over supported rhodium catalysts in supercritical carbon dioxide solvent - Hiyoshi, Norihito; Mine, Eiichi; Rode, Chandrashekhar V.; Sato, Osamu; Shirai, Masayuki (Applied Catalysis A-General, 2006)
Hydrogenation of tetralin was studied over supported rhodium catalysts in supercritical carbon dioxide solvent at 333 K. The results were compared with those in an organic solvent and under neat conditions. Higher cis-decalin yield was obtained in supercritical carbon dioxide solvent than under non-supercritical conditions. It was observed that higher hydrogen concentration at the surface in supercritical carbon dioxide solvent led to fast direct hydrogenation of tetralin to cis-decalin; the flipping of the intermediate, octalin, to give trans-decalin could be prevented. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: cis-decalin; Hydrogen storage; Hydrogenation; Supercritical carbon dioxide; supported rhodium catalysts; tetralin